Circuit training using elastic band: Can it improve the direction-changing agility of Kabaddi athletes? - Utama, Made Bang Redy; Sugiharto, Sugiharto; Hidayah, Taufiq; Mukarromah, Siti Baitul; Sutoro, Sutoro (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The ability to quickly change direction is important for kabaddi players, as it is crucial for building points and defeating opponents. The aim of this study was to determine the speed increase during change of direction after circuit training by using elastic bands with different resistance loads. We used the experimental design (pretest-posttest method). The sample consisted of 44 male Kabaddi athletes younger than 20 years old and belonging to the Junior Elite level in kabaddi, from Bali Province, Indonesia. They were divided into 4 groups based on circuit training intensity and elastic band resistance load. Each athlete received a 6-week treatment program. The data were processed through the Statistical Package for the Social Sciences (SPSS), version 24.0 (IBM, USA). The results showed that there is a statistically significant relationship between circuit training using elastic band and the athlete’s speed in changing direction. Also, it is evident that the training program with a series of high-intensity exercises using an elastic band with a resistance load of 2.27 kgf increased the speed in changing direction by 13.74%.